Uniform power transmission gears - Hlebanja, Gorazd (Strojniški vestnik, 2009)
A new type of lubricated gears is presented in this paper, referred to as Uniform Power Transmission Gears (UPTG), which have conformal shaped teeth flanks that enable a more uniform transmission of power and motion. The proposed teeth flanks comprise three arcs: an addendum arc, a dedendum arc, with both of these joined by a connecting arc. These UPT gears have been derived from Hawkinsć patented Zero Sliding Gears (YSG) 4. The name Uniform Power Transmission Gears derives from the fact that these gears operate during power transmission with an almost constant value of friction and a nearly constant value of power transmission. Thus, the power transmission of the UPT gears occurs simultaneously with the doublecontact teeth flanks of the driving and driven gears, which means the transmitted power is divided into two parts: the contact pressure in the contacts is lower, and the gear pair conjugates as helical gears. UPT gears can be produced on common gear cutting machines based on a rolling process where teeth shapes are formed by successive enveloping cuts of a cutter. However, the cutter teeth should be manufactured by the UPT rack profile. A comparison of the UPTGs with involute-type gears is presented. The radii of curvature are investigated in detail and the velocities in the teeth flank contacts were analyzed. Additionally, an investigation of oil-film thickness using the theory of Hamrock and Dowson is discussed. Owing to the decisive influence of heat caused by friction on gearsć scuffing resistance, and the heating of the teeth flanks based on Blokćs flash-temperature criterion, we have made a careful study and the results are presented. Because the power transmission with UPTGs occurs mostly by rolling, with only a minor amount by sliding, such gears are verz suitable for heavy-duty power transmission at relatively slow speed working conditions.
Keywords: zobniki; mazanje; trenje; drsenje